Comparison of ketamine nebulisation with ketamine gargle in attenuating postoperative sore throat - Misbah asghar; Amna Khan; Muhammad Taqi; Faiza; Atekah Alam; Hafeez ullah (Medical Journal of South Punjab, 2023)
Objective: to compare the effectiveness of ketamine nebulisation versus ketamine gargle in reducing the incidence and severity of postoperative sore throat (POST). Methodology: A prospective randomized study conducted at Regional headquarters hospital Skardu. Pakistan from December 2022 to November 2023, lasting for one-year duration. patients were randomly assigned into two groups, Group GK and Group NK, each comprising 45 individuals, using computer-generated random number tables. These tables were enclosed in opaque envelopes prepared by an anesthesiologist not directly involved in the study. Results: Mild sore throat occurred in GK group at 0, 2, 4, and 24 hours post-op at 4.4%, 4.4%, 6.7%, and 4.4%, respectively. In Group NK, it was 6.7%, 8.9%, 8.9%, and 6.7% at the same intervals. Moderate sore throat in GK was 6.7%, 2.2%, 2.2%, and 0%, and in NK was 2.2%, 6.7%, 0%, and 0%. The difference in sore throat severity between groups was statistically insignificant (p > 0.050). Conclusion: Ketamine nebulization is widely accepted by all patients and has proven effective in reducing the incidence and severity of postoperative sore throat (POST) during the early recovery period, providing valuable assistance to anaesthetists in managing this common issue.